American journalism, 1959 - 1975 (New York, NY, 2000)
This books is the distilled nectar from the two volume hardbound series issued earlier. While I haven't read the above-mentioned 2 volumes, I have read enough other Vietnam material to authoritatively state that this book does a more than adequate, dare I say brilliant, job of crystallizing the plethora of intertwined issues that encompassed the Vietnam war and the world stage upon which it unfolded. This book also offers some very unpleasant lessons to those of us who found our way to it due to the recent round of warfare commenced by the Bush Administration in order to save the world from Communism, ummm, I mean Terrorism.
Keywords: Vietnamese conflict, 1961 - 1975,Journalism; ress coverage; 20th century; United States,United States